Inverse kinematic analysis of the shipborne launcher - Trần, Xuân Diệu (Journal of Military Science and Technology, 2022)
In this paper, the reverse kinematic model of the shipborne launcher with the stabilized elevation and azimuth angle is investigated. These results are motion laws of the elevation and azimuth shaft angle determined. These rules are the basis for the design of the controller and the mechanical design of this type of launcher.